Truce : the day the soldiers stopped fighting - Murphy, Jim, 1947- (New York : Scholastic, 2009)
Describes the Christmas truce that occurred along Western Front trenches in 1914 and features quotations from young men on both sides, a timeline, and additional source material.
Those stupid kings and emperors -- Things were beginning to look unpleasant -- All attacks are to be pushed to the extreme -- There is no longer any sense in this business -- It was a sight one will never see again -- The lull is finished -- Epilogue.
Keywords: Christmas Truce, 1914 -- Juvenile literature; World War, 1914-1918 -- Campaigns -- Western Front -- Juvenile literature; World War, 1914-1918 -- Armistices -- Juvenile literature; Christmas Truce, 1914.; World War, 1914-1918 -- Campaigns -- Western Front; World War, 1914-1918 -- Armistices